Thoracic endometriosis masquerading as Meigs' syndrome in a young woman: A case report and literature review - Vishal Bahall; Lance De Barry; Keevan Singh (Elsevier, 2022)
Thoracic endometriosis is an exceedingly rare condition characterized by the presence of endometriotic deposits on the diaphragm, lungs or pleural space. Patients may present with massive hemothorax, pneumothorax, hemoptysis or pulmonary nodules. It is a complex condition that often proves to be a diagnostic challenge, resulting in under-diagnosis, delays in treatment and significant morbidity in women of reproductive age. We report a case of endometriosis causing massive pleural effusion and ascites, with a left adnexal fibroid mass mimicking Meigs' syndrome in a nulliparous woman in her late 30s. The patient was successfully managed with hormonal therapy following fertility-sparing surgical treatment. This case highlights the diagnostic and therapeutic challenges associated with thoracic endometriosis because of its close resemblance to more sinister gynecological conditions. Hormonal therapy is the long-term treatment of choice in patients with thoracic endometriosis to reduce the risk of symptom recurrence and preserve fertility.